Molecular docking studies of phytochemicals from azadirachta indica with trehalose–6-phosphate phosphatase of pathogenic microbes - Azmihan, Adam; Johari, Nurul Anis; Abdullah, Mohamad Zakkirun; Bakar, Latifah Munirah (Malaysian Institute of Chemistry, 2024)
Trehalose-6-phosphate phosphatase (TPPs) is a particular enzyme involved in the biosynthesis pathways of trehalose that are often connected to the virulence of pathogenic microbes. Therefore, TPPs are targeted for therapeutic purposes. The inhibition of its biosynthesis pathway can achieve this. Azadirachta indica (A. indica), despite its wide use in traditional medicine, received less attention when studying the bioactive compounds for antimicrobial properties. Therefore, this study aims to investigate the potential of phytochemicals from Azadirachta indica as a therapeutic agent against TPPs of pathogenic microbes via in silico analysis. Molecular docking was conducted using 30 selected phytochemicals from A. indica against TPPs from Candida albicans (PDB: 5DXI), Cryptococcus neoformans (PDB: 5DX9), and Salmonella Typhimurium (PDB: 6UPD) with ampicillin, fluconazole, and isoniazid acting as control ligand. Molecular docking was performed using AutoDock Vina. The molecular docking analysis indicates that phy